Comparação entre os valores de limite de liquidez obtidos pelos métodos de Casagrande e cone para diferentes solos argilosos - Crevelin, Letícia Garcia (2018)
In this present study, is highlighted the importance of specifying the procedure and equipment used to determine the liquid limit (LL) of a clay soil. The results of LL, obtained by percussion method proposed by Casagrande (LLc) and by the cone penetration method (LLp), measured by different operators and at different laboratories of clayey soils from different mineralogies and geological origins were compared. The LLp values were determined using British cone (20 mm fall cone penetration) and LLc values were determined using different hardnesses of Casagrande apparatus. Eight data base groups of LLc and LLp were evaluated, grouped according to the hardness of the percussion apparatus, mineralogy and LL value of the clayey soils. The experimental results using simple linear regression shows that the correlations between the two methods vary with the mineralogy of the clayey soil and the hardness of the base of the apparatus to the percussion. The liquid limit results obtained for kaolinites and ilites or low LL soils indicated LLp > LLc. The LL results of montmorillonites or soils with high LL value showed that there is greater dispersion among the correlations between both methods and that LLp < LLc. Residual statistical tests showed that, despite the high values of determination coefficients obtained, some linear correlations defined in this study are not valid or should be used with caution. The correlations were valid for montmorillonites (for clay content higher than 30%) and for clayey soils of several mineralogies with LL between 20-80% (this only for hard base percussion apparatus). It should be emphasized that this study seeks to stimulate the critical evaluation of the previously published correlations and those that will be elaborated in the future, and not to exhaust the subject about obtaining correlations between geotechnical tests